Analysis Of Factors Affecting Brand Image and Its Impact on Honda Adv Motorbikes Purchasing Interest in Semarang City - Ryan Arya Pramudya; I Made Sukresna (SEIKO : Journal of Management & Business, 2021)
Abstrak The rapid development of the world of technology has an impact on a high level of competition, including the competition for motorcycle sales. One that competes is the Honda ADV motorcycle, which strives to continue to be the choice of consumers, including in the city of Semarang. ADV products themselves are still trying to be accepted by consumers, especially in the city of Semarang. However, the increasing number of choices of other motorcycle products has an impact on the sales of Honda ADV products that have not met the target and often experience a decrease in sales, so it must be able to improve its marketing strategy through price, promotion and quality of service provided. The purpose of this study was to determine the effect of price, promotion, and service quality on brand image and purchase intention. The population in this study were 150 respondents who had visited the dealer and received information about Honda products and the sampling technique used was purposive sampling. The data collection method is done through a questionnaire. The results of the analysis show that each hypothesis has a significant positive impact. Problems can be overcome if the company pays attention to factors such as price, promotion, and service quality, as well as brand image. Kata Kunci: Service Quality, Brand Image, Purchase Intention, Consumer Behaviour